ANALISIS IMPLEMENTASI TEKNOLOGI DIGITAL PADA USAHA MIKRO KECIL MENENGAH DI WILAYAH PERBATASAN - Veneranda Rini Hapsari; Usman Usman; Benedhikta Kikky Vuspitasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to find out how much digital technology is used in the marketing field for micro, small and medium enterprises in border areas, especially Bengkayang district. This research is a qualitative descriptive study, using the methods of observation, interviews and documentation. The results of community research in Bengkayang Regency have used digital technology as a means of marketing products, but in implementing the management of marketing products it is still relatively low, because of problems in the network so that there is still use through manuals directly to consumers, although purchasing power is lower than using digital marketing technology.